"If you stare at it from above" (Phd. 110b). Platonic stereometry, a paradigm to think about the Anthropocene - Lanza González, Henar (2023)
Due to the importance of extractivist phenomena in the Anthropocene, I propose to stop looking at the Earth from theparadigm of flat geometry, which prevents us from seeing the relationship between energy needs, resources and freedom, and to adopt a stereometric one inspired by the curriculum of the guardians of the Republic. To this end, I will explore the two facets of the Earth, Gaia and Chthón, and will do a triple exercise of katabasis to read several eschatological myths in an energetic, political and temporal key.